Uji performa hybrid turbin angin savonius-darrieus eggbeater - Delffika Canra; Rachmatullah Rachmatullah (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
The development of the Vertical Axis Wind Turbine (VAWT) is still a challenge for several researchers in the world and in Indonesia. Due to the potential of the Indonesian coast generally has an average wind speed of 3-7 m / s which is classified as low wind speed and is very suitable for VAWT which operates at low wind speeds. Combining the 2 existing VAWT types is one of the development efforts on VAWT to improve the performance of these wind turbines. Hybrid VAWT Savonius-Darrieus can increase the coefficient of performance (Cp) where the maximum Cp of savonius is 30% while Darriues is 35%. There have been several researchers making the Savonius-Darrieus Hybrid VAWT prototype producing Cp above 35%, but this is still far from the ideal Cp of wind turbines around 59%. The combination variation of 2 types of VAWT still has the opportunity to be investigated with various variations in construction and variations in additional accessories. The research method that will be carried out is the prototype experimental method, with the design and prototyping stages. The prototype was tested at the Mechanical Engineering Laboratory of the Indramayu State Polytechnic by blowing the wind at a certain speed from the wind tunnel that had been prepared in advance. There were 11 samples prepared, namely 4 samples for 3 levels and 7 samples for 4 levels. There were 5 samples that reached a Cp value of 0.58 which was close to the ideal Cp value, but there was no increase in TSR in all samples.